Analysis Of The Impact Of Macroeconomic Policies On Economic Growth In Indonesia (2010-2022) - Lastri, Lastri; Purba, Elvis F; Sihotang, Jusmer; Gea, Putri Angeline (Jurnal Ilmu Sosial Mamangan, 2025)
Economic growth is a difficult problem for every country to overcome. The government can use macroeconomic policies, namely monetary policy and fiscal policy, to increase economic growth. The monetary policy instruments used in this research are JUB, BI rate, inflation and exchange rate, while fiscal policy is in the form of taxes and government spending. By using the VAR method, JUB and the exchange rate have a significant influence on economic growth and in the long term increasing JUB and stabilizing the exchange rate can increase economic growth while high inflation and BI rates can reduce economic growth. When the economy is sluggish, the government can increase the JUB by reducing the Minimum Statutory Reserve and carrying out open market operations, limiting imports and increasing exports so that the rupiah exchange rate against the dollar can appreciate so that inflation can be suppressed, then lowering the interest rate on savings and loans so that people can running MSMEs or macro businesses. In the long term, fiscal policy in increasing tax revenues from the formal sector and increasing government spending in infrastructure development, education and health can increase economic growth.